Gender Moderation in Entrepreneurial Knowledge and Self-Efficacy: Implications for Student Business Interests: Moderasi Gender dalam Pengetahuan Kewirausahaan dan Efikasi Diri: Implikasi untuk Minat Bisnis Mahasiswa - Purnamasari, Afinda Eka; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2023)
This quantitative study investigates the influence of gender as a moderator on entrepreneurial knowledge and self-efficacy and their impact on students' business interests at Muhammadiyah University of Sidoarjo. Data were collected from 210 randomly sampled respondents using questionnaires. Our analysis reveals that gender indeed plays a significant moderating role in shaping the relationship between entrepreneurial knowledge, self-efficacy, and students' business interests. This research sheds light on the gender-specific dynamics within entrepreneurship education, highlighting the need for tailored approaches to foster students' entrepreneurial aspirations and capabilities. Highlights: Gender moderates entrepreneurial knowledge and self-efficacy. Quantitative study with 210 student respondents. Implications for tailored entrepreneurship education. Keywords: Gender, Entrepreneurship Education, Self-Efficacy, Business Interests, Moderation